2018
DOI: 10.1021/acs.inorgchem.8b02049
|View full text |Cite
|
Sign up to set email alerts
|

Post-synthetic Modification of a Two-Dimensional Metal–Organic Framework via Photodimerization Enables Highly Selective Luminescent Sensing of Aluminum(III)

Abstract: Reaction of Cd­(NO3)2·4H2O with 5-fluoro-1,3-bis­[2-(4-pyridyl)­ethenyl]­benzene (5-F-1,3-bpeb) and 1,3-benzene­dicarboxylic acid (1,3-H2­BDC) under the solvothermal conditions gave rise to a two-dimensional metal–organic framework (MOF) [{Cd2­(5-F-1,3-bpeb)2­(1,3-BDC)2}·0.5DMF·2H2O] n (1). Compound 1 was postmodified by a photodimerization reaction between 5-F-1,3-bpeb ligands to yield [{Cd2­(syn-dftpmcp)­(1,3-BDC)2}·0.5DMF·H2O] n (syn-dftpmcp = syn-3,4,­12,13-tetrakis­(4-pyridyl)-8,17-bisfluoro-1,2,­9,10-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(30 citation statements)
references
References 92 publications
0
30
0
Order By: Relevance
“…Besides the unidirectional dimerization reaction, the attempt on reverse cleavage of cyclobutane ring in 2 was further explored. According to some recent work, higher wavelength light irradiation or heating of the cyclobutane product could be used to achieve the inversion process [7,[13][14][15][16][17]. However, after 2 days irradiation of the polycrystalline samples 2 by a 50 W low-pressure Hg lamp (λ= 254 nm), the PXRD patterns (Figure S10) and IR spectra (Figure S11) of the irradiation sample show no apparent change in comparison to the initial data, indicating an inert reactivity.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Besides the unidirectional dimerization reaction, the attempt on reverse cleavage of cyclobutane ring in 2 was further explored. According to some recent work, higher wavelength light irradiation or heating of the cyclobutane product could be used to achieve the inversion process [7,[13][14][15][16][17]. However, after 2 days irradiation of the polycrystalline samples 2 by a 50 W low-pressure Hg lamp (λ= 254 nm), the PXRD patterns (Figure S10) and IR spectra (Figure S11) of the irradiation sample show no apparent change in comparison to the initial data, indicating an inert reactivity.…”
Section: Resultsmentioning
confidence: 98%
“…However, in most cases, only the unidirectional photochemical [2+2] cycloaddition reaction is reported. The reversible cleavage of the cyclobutane ring to the olefins [7,[13][14][15][16][17], which is necessary for potential applications in photoswitching, optical recording, and sensing, has rarely been explored.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, MOF2 has a higher selectivity than MOF1 in the detection of Al 3+ (Figure 9). [102] Li's team has synthesized three new MOF materials, among which the first MOF1 has 2D topology, and the second and third MOF2 and MOF3 have three‐dimensional topology [103] . MOF1‐2 shows strong luminescence and high stability in water.…”
Section: Sensorsmentioning
confidence: 99%
“…The prepared MOFs and its photopolymerized derivative were found to be selective for the detection of Al 3+ ions through a luminescence quenching approach with a detection limit of 183 ppb. [149] Han et al have reported that [Cd 2 (OBA) 2 (BPTP)(H 2 O)] with BPTP is a V-shaped thienylpyridyl ligand and OBA is 4,4′-oxidibenzoic acid, which showed a dual-responsive luminescent probe for Fe 3+ and Al 3+ ions in DMF suspension. [150]…”
Section: Zinc and Aluminum Detectionmentioning
confidence: 99%